Apple intake is inversely associated with all-cause and disease-specific mortality in elderly women. Issue 5 (20th January 2016) - Hodgson, Jonathan M.; Prince, Richard L.; Woodman, Richard J.; Bondonno, Catherine P.; Ivey, Kerry L.; Bondonno, Nicola; Rimm, Eric B.; Ward, Natalie C.; Croft, Kevin D.; Lewis, Joshua R.
Abstract: Higher fruit intake is associated with lower risk of all-cause and disease-specific mortality. However, data on individual fruits are limited, and the generalisability of these findings to the elderly remains uncertain. The objective of this study was to examine the association of apple intake with all-cause and disease-specific mortality over 15 years in a cohort of women aged over 70 years. Secondary analyses explored relationships of other fruits with mortality outcomes. Usual fruit intake was assessed in 1456 women using a FFQ. Incidence of all-cause and disease-specific mortality over 15 years was determined through the Western Australian Hospital Morbidity Data system. Cox regression was used to determine the hazard ratios (HR) for mortality. During 15 years of follow-up, 607 (41·7 %) women died from any cause. In the multivariable-adjusted analysis, the HR for all-cause mortality was 0·89 (95 % CI 0·81, 0·97) persd (53 g/d) increase in apple intake, HR 0·80 (95 % CI 0·65, 0·98) for consumption of 5–100 g/d and HR 0·65 (95 % CI 0·48, 0·89) for consumption of >100 g/d (an apple a day), compared with apple intake of <5 g/d ( P for trend =0·03). Our analysis also found that higher apple intake was associated with lower risk for cancer mortality, and that higher total fruit and banana intakes were associated lower risk of CVD mortality ( P <0·05). Our results support the view that regular apple consumption may contribute to lower risk of mortality.